Flooding of an ancient ship during the shipwreck - Rudan, Smiljko; Sviličić, Šimun (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Shipwrecks are the remnants from the past that contain the story about the ship, sailors, cargo, and some aspects of the world of that time. A shipwreck also acts as evidence of the event, usually tragic, that brought the ship’s life to end. Depending on the evidence from the archaeological site, various reasons for the sinking of the ship can be examined. State-of-the-art engineering tools may be used to simulate the events leading to a shipwreck. In this article, numerical modelling and analysis are applied to calculate flooding time until the loss of buoyancy of the idealised ancient vessel, which precedes the inevitable sinking. The paper aims to assess the questions about how much time is needed in various scenarios for the sections of an ancient ship to get flooded, and how the internal design of the ship influences the flooding time.